One morning in July the man who was first on the scene tells his story about the day that changed London forever - Debnam, Aaron (John Blake, 2007)
Offers an insight into a terrorist attack that shocked the whole country and reminds us that, even in the face of a tragedy of such devastating proportions, the goodness of the human spirit can still shine through. This work also explores the lasting effect that the attacks had on Aaron.